Implementasi Kebijakan Pemberian Air Susu Ibu Ekslusif di Puskesmas - Magda Marieke Munaiseche; Freddy Wagey; Nelly Mayulu (Universitas Sam Ratulangi, 2021)
Background: The low understanding of mothers, families and the community about the importance of breastfeeding for babies and the absence of support or regulations at the district / city level has resulted in the exclusive breastfeeding program not running well. The purpose of this study was to analyze the implementation of Government Regulation No. 33/2012 concerning the Giving of Exclusive Asi in Bitung City. Method: This research uses qualitative research methods, using primary data and secondary data. The informants in this study were 13 people. The method of research is through in-depth interviews and document observation, then recorded in the form of a transcript and then the data is presented in a matrix. The data were analyzed using source triangulation, method triangulation, and data triangulation techniques. Results: The results show that there are no regulations that support the implementation of PP 33 of 2012 on exclusive breastfeeding in Bitung City, there are no trained counselors, information about exclusive breastfeeding is still lacking, Posyandu cadres have not been involved in providing outreach on exclusive breastfeeding, lack of supervision as well as guidance for midwives so that there is still the sale of formula milk to breastfeeding mothers, the availability of nursing room facilities / facilities is not evenly distributed because it is only at the puskesmas level. Conclusion: The conclusion of this research is that the implementation of the policy on exclusive breastfeeding in the city of Bitung has not yet been implemented in accordance with Government Regulation number 33 of 2012.